Evaluation of the implementation of the Adiwiyata program at State Senior High School 4 Bogor - Atep Kartiansyah; Ihsana El Khuluqo; Sri Astuti; Muhammad Heru Iman Wibowo; Mirlanda Diaz Pratiwi; Azizah Nurul Khoirunnisa (Himpunan Pengembang Kurikulum Indonesia, 2025)
The Adiwiyata program, as part of environmental education in schools, plays an important role in shaping students’ ecological awareness. This study aims to evaluate the implementation of the Adiwiyata Program at SMA Negeri 4 Bogor, which has been designated as a National Adiwiyata School since 2022. The evaluation was conducted to monitor the sustainability of environmentally based programs that strengthen students’ environmental awareness and character. The research employed the CSE-UCLA evaluation model, covering five key areas: system assessment, program planning, program implementation, program improvement, and program certification. A qualitative research approach was used, involving interviews, focus group discussions, observations, and document analysis to obtain a comprehensive understanding of the program implementation. The findings indicate that SMA Negeri 4 Bogor has successfully implemented the Adiwiyata Program through well-integrated policies within the curriculum, structured planning, and environmental activities involving school members and external partners. Program improvement is demonstrated through the use of environmentally friendly products, capacity-building initiatives, and collaboration with local government programs. The program has also contributed to enhancing students' environmental awareness and character development. However, further efforts are needed to expand students' environmental awareness and character development, strengthen partnerships, and optimize the use of environmentally friendly technology to ensure long-term program sustainability. Abstrak Program Adiwiyata sebagai bagian dari pendidikan lingkungan hidup di sekolah memiliki peran penting dalam membentuk kesadaran ekologis murid. Penelitian ini dilakukan untuk mengevaluasi implementasi Program Adiwiyata di SMA Negeri 4 Bogor sebagai Sekolah Adiwiyata Nasional sejak tahun 2022. Evaluasi ini dilatarbelakangi oleh pentingnya pemantauan keberlanjutan program berbasis lingkungan demi penguatan karakter peduli lingkungan pada warga sekolah. Penelitian menggunakan model evaluasi CSE-UCLA yang mengkaji lima area utama, yaitu asesmen sistem, perencanaan program, pelaksanaan program, pengembangan program, dan sertifikasi program. Pendekatan penelitian kualitatif diterapkan melalui wawancara, diskusi terarah, observasi, dan studi dokumentasi untuk memperoleh gambaran pelaksanaan program secara komprehensif. Hasil penelitian menunjukkan bahwa SMA Negeri 4 Bogor telah menerapkan Program Adiwiyata dengan baik melalui kebijakan yang terintegrasi dengan kurikulum, perencanaan terstruktur, serta pelaksanaan berbagai kegiatan berbasis lingkungan yang melibatkan warga sekolah dan mitra eksternal. Inovasi pengembangan program terlihat pada pemanfaatan produk ramah lingkungan, penguatan kompetensi, serta sinergi dengan program pemerintah daerah. Program ini juga berkontribusi pada peningkatan kesadaran lingkungan dan karakter murid. Namun demikian, diperlukan upaya lebih lanjut dalam memperluas nilai keberlanjutan dalam pembelajaran, memperkuat kemitraan, dan optimalisasi teknologi ramah lingkungan agar program dapat terus berkelanjutan. Kata Kunci: Adiwiyata; CSE-UCLA; evaluasi program; keberlanjutan; sekolah berwawasan lingkungan